The Relationship Between Family Social Support And Post-Traumatic Growth In People With Hiv/Aids (Plwha) In Semarang City - Amalia, Firja Atifah; Widyati, Sri (Jurnal Riset Kesehatan, 2025)
This study aims to empirically examine the relationship between family social support and post-traumatic growth in people living with HIV/AIDS (PLWHA) in the city of Semarang. The hypothesis proposed is that higher levels of family support are positively associated with greater post-traumatic growth. The participants were PLWHA aged 20-50 years who live in Semarang City (N=94). Participants completed the Post-Traumatic Growth Scale and Family Social Support Scale via Google Form using a correlational quantitative research method with purposive sampling. The data analysis using Spearman's rho correlation revealed a significant positive relationship (rho = 0.470; p=0.000 (p<0.01) between the two variables. These findings support the hyphotesis and highlight the importance of family support in enhancing psychological resilience and positive transformation among PLWHA.